Financial Incentives, Fertility, and Son Preference in Armenia - Pinto, Maria Florencia (World Bank, Washington, DC, 2021)
Armenia experienced dramatic demographic changes in the past three decades: the share of adults age 65 and over nearly doubled, the total fertility rate reduced by more than 30 percent, and the male-to-female sex ratio at birth increased to one of the world’s highest. Like other middle-income countries concerned with the implications of an aging population for long-term growth and fiscal sustainability, Armenia introduced financial incentives to promote fertility. This paper estimates the effect of the 2009 reform of the universal Childbirth Benefit Program, which increased the amounts of lump sum transfers conditional on birth. The analysis relies on a quasi-experimental strategy exploiting the timing of the policy change and eligibility rule—women get a larger transfer for third and higher-order births. The findings show that the annual probability of an additional birth among women with at least two other children increased between 1.4 and 1.6 percentage points in the five years following the policy change. These effects are equivalent to 58 and 64 percent of the pre-reform birth probability for women who had at least two children. Given the previously demonstrated relationship between fertility level and sex ratio in societies with strong son preference, the reform may potentially alleviate the sex imbalance without directly targeting it. Parents who already have at least one son and are less likely to engage in sex selection and more likely to have additional births; however, the findings do not indicate a significant increase in the likelihood of having daughters.